(untitled) (American Journal of Islam and Society, 1997)
Thi publication comes at a time when unprecedented bloody ethnic conflict not only dominate the global media and international politics, but also numb the world’s conscience. Bosnia Herzegovina, Somalia, Rwanda, Burundi, East Timor, Chechnia, Kashmir, and Kurdistan are some of the famous landmarks where entire countries and communities are caught up in the web of ethnic conflict. In other instances, ethnic conflict is gradually becoming a feature of national life. It is not at all unfamiliar to hear reports of ethnic conflict in India (Hindu-Muslim riots), Germany (violence against immigrant Turks), France (anti-Arab right-wing nationalist fervor and the Muslim scarf issue), the United States (Los Angeles riots after the Rodney King trial) and Great Britain (Muslim and government standoff over Salman Rushdie’s Satanic Verses). Gurr and Harff have written a useful book that tries to make sense of the causes of ethnic conflict in different parts of the world. It deals with the issue in the context of rapid changes in the world order; the emergence of ethnopolitical groups or ethnoclasses; the struggles for either autonomy or pluralism by various ethnic and social groups; the challenges that ethnopolitics poses to the international. legal and political systems; and the effect of this on communities demanding ethnic rights. It also attempts to provide a framework for analysis ...